Determinants and Systemic Consequences of International Capital Flows - Folkerts-Landau, D. (Occasional Papers; Occasional Paper ;, 1991)
The growing integration of capital markets has strengthened incentives for greater international coordination of economic and financial policies. Structural changes in these financial market, however, may have undermined the effectiveness of monetary and fiscal policy and complicated market access by developing countries. These are among the findings of this study of capital flows in the 1970s and the 1980s.